Agricultural productivity: A changing global harvest - Fuglie, Keith O.; Nin-Pratt, Alejandro (International Food Policy Research Institute, 2013)
In 1961 the world was feeding 3.5 billion people by cultivating 1.37 billion hectares of land. A half century later, the world population had doubled to 7 billion while land under cultivation increased by only 12 percent to 1.53 billion hectares. How, then, did agricultural production triple? By increasing productivity. By getting more output from existing resources, global agriculture has grown, proving wrong past concerns that the world’s population would exceed its food supply. In fact, at the global level, the long-run trend since at least 1900 has been one of increasing food abundance: in inflation-adjusted dollars, food prices fell by an average of 1 percent per year over the course of the 20th century (Figure 1). But then, over the past decade, something changed.